Posterior fossa metastasis of retinoblastoma accompanying a supratentorial second focus in a child: a case report - Yakar, Fatih; Dogan, Ihsan; Ozyurek, Elif; Ozgural, Onur; Eroglu, Umit; Bozkurt, Melih (International Surgery Journal, 2017)
The central nervous system, as a metastatic focus, has an extreme predisposition to retinoblastoma and has been indicated as the most common site for this disease. Herein, we report a 4-year-old girl presenting with multiple cranial metastases of retinoblastoma. To our knowledge, this presented case is valuable and significant in terms of being reported as the first cerebellar metastasis of retinoblastoma in the literature and removing this lesion together with supratentorial focus in a single operation with a single skin incision.